A large cohort study of the effects of Lewis, ABO, 13 other blood groups, and secretor status on COVID‐19 susceptibility, severity, and long COVID‐19. Issue 1 (3rd November 2022) - Moslemi, Camous; Sækmose, Susanne; Larsen, Rune; Brodersen, Thorsten; Didriksen, Maria; Hjalgrim, Henrik; Banasik, Karina; Nielsen, Kaspar R.; Bruun, Mie T.; Dowsett, Joseph; Kasperen, Kathrine A.; Mikkelsen, Susan; et al.
Abstract: Background: Previous studies have reported Blood type O to confer a lower risk of SARS‐CoV‐2 infection, while secretor status and other blood groups have been suspected to have a similar effect as well. Study design and methods: To determine whether any other blood groups influence testing positive for SARS‐CoV‐2, COVID‐19 severity, or prolonged COVID‐19, we used a large cohort of 650, 156 Danish blood donors with varying available data for secretor status and blood groups ABO, Rh, Colton, Duffy, Diego, Dombrock, Kell, Kidd, Knops, Lewis, Lutheran, MNS, P1PK, Vel, and Yt. Of these, 36, 068 tested positive for SARS‐CoV‐2 whereas 614, 088 tested negative between 2020‐02‐17 and 2021‐08‐04. Associations between infection and blood groups were assessed using logistic regression models with sex and age as covariates. Results: The Lewis blood group antigen Le a displayed strongly reduced SARS‐CoV‐2 susceptibility OR 0.85 CI[0.79–0.93] p  < .001. Compared to blood type O, the blood types B, A, and AB were found more susceptible toward infection with ORs 1.1 CI[1.06–1.14] p  < .001, 1.17 CI[1.14–1.2] p  < .001, and 1.2 CI[1.14–1.26] p  < .001, respectively. No susceptibility associations were found for the other 13 blood groups investigated. There was no association between any blood groups and COVID‐19 hospitalization or long COVID‐19. No secretor status associations were found. Discussion: This study uncovers a new association to reduced SARS‐CoV‐2 susceptibility for Lewis type Le a and confirms the previous link to blood group O. The new association to Le a could be explained by a link between mucosal microbiome and SARS‐CoV‐2.